Green synthesis of gold nanoparticles from Scutellaria barbata and its anticancer activity in pancreatic cancer cell (PANC‐1) - Lei Wang; Jianwei Xu; Ye Yan; Han Liu; Thiruventhan Karunakaran; Feng Li (Artificial Cells, Nanomedicine, and Biotechnology)
Nanotechnology has been materialized as a proficient technology for the development of anticancer nanoparticles all the way through an environment-friendly approach. Conventionally, nanoparticles have been assembled by dissimilar methods, but regrettably rely on the negative impact on the natural environment. Amalgamation of nanoparticles by means of plant extract is alternate conservative methods. Scutellaria barbata species was used majorly as food or as medicines against various diseases, and extensive research was conducted for their therapeutic properties. The present research was mainly focused on the synthesis of gold nanoparticles from the Scutellaria barbata by green route method and evaluation of its anticancer activity against pancreatic cancer cell lines (PANC-1). The gold nanoparticles have been characterized by UV–visible spectroscopy, TEM, SAED, AFM, and FTIR analysis. The synthesized gold nanoparticles (AuNPs) possessed effective anticancer activity against pancreatic cancer cell lines (PANC-1). Hence, further research on this plant may lead to the development of novel anticancer drugs which can be used to combat pancreatic cancer.